Necrotizing Infiltrative Lipomatosis in a Miniature Zebu Bull (Bos primigenius indicus) - Scott D. Reed; Dawn E. Evans (Veterinary Medicine International)
Lipomatosis is described in a miniature Zebu, Bos primigenius indicus, bull that died of perianesthetic complications. This is the first pathologic description of lipomatosis that we are aware of in this species and breed of cattle. Infiltration of multiple visceral organs is described and depicted along with comparison to previously published cases of lipomatosis in other breeds of cattle.